Learning from each other refining the practice of teaching in higher education - Kozimor-King, Michele, 1971-; Chin, Jeffrey C. (Jeffrey Chuan-che) (University of California Press, 2018)
"Learning from Each Other includes 20 original chapters written by well-known experts in the field of teaching and learning. Conceived for both new and experienced faculty at community colleges, four-year institutions, and research-intensive universities, the volume also addresses the interests of faculty and graduate students in programs designed to prepare future faculty and campus individuals responsible for faculty professional development. With the aim of cultivating engagement amongst students and deepening their understanding of the content, topics covered in this edited volume include: employing the science of learning in a social science context understanding the effects of a flipped classroom on student success pedagogical techniques to create a community of inquiry in online learning environments the risks and rewards of co-teaching reaching and teaching "non-traditional" students facilitating learning and leadership in student team projects connecting students with the community through research issues of assessment, including backward design, developing and using rubrics, and defining and implementing the scholarship of teaching and learning Through Learning from Each Other, all faculty who care about their teaching, but especially faculty in the social sciences, can successfully employ curricular innovations, classroom techniques, and advances in assessment to create better learning environments for their students"--Provided by publisher.